Microscopic characteristics and geological significance of pyrite in shales of the Wufeng-Longmaxi formations, southeastern Chongqing, China - Cai, Xiao; Xia, Wei; Liu, Yuxia; Liao, Shunzhou; Zhang, Lei; Hu, Weixue; Liu, Li; Li, Wei; Zeng, Fanwu (Energy Geoscience, 2024)
Shales of the Wufeng-Longmaxi formations in the basin-margin transition zone of southeastern Chongqing, China are characterized by high organic matter content and a significant presence of pyrite development. By examining numerous scanning electron microscope (SEM) images and considering the crystal and aggregate characteristics of minerals, we identified four types of pyrite in the study area: euhedral crystals, irregular aggregates, framboidal aggregates, and metasomatized organisms. Among these types, framboidal aggregates are the most prevalent. The formation mechanism of framboidal pyrite can be categorized into inorganic and organic origins. As inferred from the pyrite characteristics in the study area, the formation mechanism of the metasomatized organisms aligns with the biologically induced mineralization mode of organic origin, whereas the framboidal aggregates are more associated with the biologically controlled mineralization mode of organic origin. This underscores a close relationship between the pyrite formation and organic matter, which in turn indicates that an organic origin is more consistent with the pyrite characteristics observed in this study area. The pyrite morphology can reflect reactive iron concentration. Euhedral pyrite crystals tend to form under a low reactive iron concentration, whereas the formation of framboidal pyrite requires a high reactive iron concentration. Additionally, the type and grain size of pyrite aggregates can reflect variations in the redox conditions of the depositional environment. Pyrite produces positive effects on reservoir storage space, with intercrystalline organic pores, intercrystalline pores, and mold pores associated with pyrite contributing greatly to the storage spaces. [Display omitted] •Pyrite crystal forms from Longmaxi Formation shale analyzed with SEM.•Genesis of pyrite explored based on morphology and structure.•The shape and grain size of framboidal pyrites indicate oxidation and reduction in different areas.